2013 International Conference on Interactive Collaborative Learning (ICL) 2013
DOI: 10.1109/icl.2013.6644565
|View full text |Cite
|
Sign up to set email alerts
|

Gamification-based assessment of group work

Abstract: The importance and benefit of group work is nowadays widely recognized and acknowledged in education. Group work can be supported by online shared workspaces that allow group collaboration. However, the e-assessment of group work remains an issue. Most of the existing strategies rely on intra-group peer assessment to evaluate individual contribution to group work. We propose an alternative by introducing some gamification components. The assessment of students' individual involvement and performance is then sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 12 publications
1
19
0
3
Order By: Relevance
“…Over the years, there have been attempts to apply game-based learning to education in order to stimulate students to behave well towards education (Denny, 2013). The goal is to make students participate in all activities that have to do with the various learning areas, encouraging them to use teaching aids that appeal to them (Denny, 2013;Domínguez et al, 2013;Moccozet, Tardy, Opprecht, & Léonard, 2013;Simões, Redondo, & Vilas, 2013).…”
Section: Gamification In Educationmentioning
confidence: 99%
“…Over the years, there have been attempts to apply game-based learning to education in order to stimulate students to behave well towards education (Denny, 2013). The goal is to make students participate in all activities that have to do with the various learning areas, encouraging them to use teaching aids that appeal to them (Denny, 2013;Domínguez et al, 2013;Moccozet, Tardy, Opprecht, & Léonard, 2013;Simões, Redondo, & Vilas, 2013).…”
Section: Gamification In Educationmentioning
confidence: 99%
“…A study by Davis and Klein (2015) with high school students found that digital badges were recognised as an opportunity for personal empowerment but the students had concerns about the sharing of digital badges online. In the higher education sector, digital badges have been explored as an alternative to grades (micro-credentialing) (Elliott et al, 2014); supporting the process of progressing through research degrees (Mewburn et al, 2014); assessing individual students in collaborative assignments (Moccozet, 2013); and as an introduction to navigating a physical campus through a scavenger hunt exploration (Koutropoulos, 2012). This wide range of activities identifies that there are highly creative uses of digital badges in the higher education sector.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Such scores and rewards influence motivation and engagement and downgrade free riders (Moccozet, Tardy, Opprecht, & Leonard, 2013). Other tools that might be used to motivate group work engagement include conversational agents as a means of creating awareness or changing user behavior in relation to a specific goal (e.g.…”
Section: Implications For Practicementioning
confidence: 99%